Pengaruh Manfaat Dasar, Fisik & Tambahan Pada Perilaku Pembelian Tabloid Soccer - A.Sigit Pramono Hadi (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2016)
The fierce competition in sport magazine industry cause the creativity of strategic marketing to manipulate on how to keep the loyality of their audience and exist in media industry. This research aims to give descriptions and explanation of correlation between variables : Basic Gratifications (X1) Physical Gratifications (X2). More others Gratifications (X3) and Duplication Purchasing Behaviour Soccer magazine (Y). by using regression statistic analysis, the results shows that hypothesis on this research is rejected. This means that there is no correlations between interdependent varibles with duplication purchasing behavior audience. Base on this results we suggest to media industry to create innovation and use modern technology of information and communication to challenge their market share in industrial market media and to keep their audience loyalty and increase of their sastifactions. For more studies this research can use and Gratifications theory to explore moe the gratification Sought and Gratification Obtained